The Quality of Work Life and Its Influencing Factors Among Dentists in Kashan City - Ahmadreza Alipour; Farhad Alipour; Farzad ziaee (Patient Safety and Quality Improvement Journal, 2024)
Introduction: Assessing dentists' quality of work life is vital for their well-being and the sustainability of the oral health care system. This study aims to evaluate dentists' working conditions in Kashan city and identify the factors influencing them. Materials and Methods: This descriptive study employs a survey and correlation method, targeting a statistical population of 142 dentists in Kashan City. Data was collected in the field using Walton's Quality of Work Life Questionnaire and analyzed through one-sample t-tests, independent t-tests, analysis of variance, and linear regression. Results: The quality of dentists' working life, including salary, work environment, legality, dependence, work cohesion, and personal growth, is significantly lower than the hypothetical average. Male and female dentists differ considerably in their quality of work-life scores. Still, there is no significant difference between single and married dentists, general and specialist dentists, and dentists with over 20 years of work experience. Dentists with 20 years of experience have a significantly better quality of work life compared to those with 10 years of experience. Work experience, marital status, gender, and education level account for 29% of the variance in quality of work life. Conclusion: The quality of work life of dentists in Kashan is lower than the average level and is generally unfavorable. Gender and work experience have also been influential factors.